Live-Attenuated Respiratory Syncytial Virus Vaccine With M2-2 Deletion and With Small Hydrophobic Noncoding Region Is Highly Immunogenic in Children. (1st February 2020) - McFarland, Elizabeth J; Karron, Ruth A; Muresan, Petronella; Cunningham, Coleen K; Perlowski, Charlotte; Libous, Jennifer; Oliva, Jennifer; Jean-Philippe, Patrick; Moye, Jack; Schappell, Elizabeth; Barr, Emily; Rexroad, Vivian; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is the leading viral cause of severe pediatric respiratory illness, and vaccines are needed. Live RSV vaccine D46/NS2/N/ΔM2-2-HindIII, attenuated by deletion of the RSV RNA regulatory protein M2-2, is based on previous candidate LID/ΔM2-2 but incorporates prominent differences from MEDI/ΔM2-2, which was more restricted in replication in phase 1. Methods: RSV-seronegative children aged 6–24 months received 1 intranasal dose (10 5 plaque-forming units [PFUs] of D46/NS2/N/ΔM2-2-HindIII [n = 21] or placebo [n = 11]) and were monitored for vaccine shedding, reactogenicity, RSV-antibody responses and RSV-associated medically attended acute respiratory illness (RSV-MAARI) and antibody responses during the following RSV season. Results: All 21 vaccinees were infected with vaccine; 20 (95%) shed vaccine (median peak titer, 3.5 log10 PFUs/mL with immunoplaque assay and 6.1 log10 copies/mL with polymerase chain reaction). Serum RSV-neutralizing antibodies and anti-RSV fusion immunoglobulin G increased ≥4-fold in 95% and 100% of vaccines, respectively. Mild upper respiratory tract symptoms and/or fever occurred in vaccinees (76%) and placebo recipients (18%). Over the RSV season, RSV-MAARI occurred in 2 vaccinees and 4 placebo recipients. Three vaccinees had ≥4-fold increases in serum RSV-neutralizing antibody titers after the RSV season without RSV-MAARI. Conclusions: D46/NS2/N/ΔM2-2-HindIII had excellent infectivity and immunogenicity and primed vaccine recipients for anamnestic responses, encouraging further evaluation of this attenuation strategy. Clinical Trials Registration: NCT03102034 and NCT03099291. Abstract : Live respiratory syncytial virus (RSV) vaccine D46/NS2/N/ΔM2-2-HindIII attenuated by deletion of the RSV RNA regulatory protein M2-2 had excellent infectivity and immunogenicity, and primed for anamnestic responses, encouraging further evaluation of this attenuation strategy.